Arenas públicas virtuales en Twitter y politización religiosa en Ecuador - Argüello Pazmiño, Sofía; Hurtado, Edison (El Colegio de México, 2023)
Although politics is not diluted in social media, resources for collective action and innovation of repertoires of political contention are marked by emerging interactions in the digital polis. This article analyzes a case of political activism on the legalization of same-sex civil marriage in Ecuador, leaded by pro-life religious collective actors and undertaken on Twitter in June 2019. We formulate and use analytical model on politicization mechanisms in virtual public arenas. We pinpoint three moments in this process: identification, framing and definition of the situation, and political work for advocacy. Religious politicization is described using quantitative and qualitative information.